Teach now! physical education : becoming a great PE teacher - Burton, Daniel, 1986- (London ; New York : Routledge, Taylor & Francis Group, 2018)
"This book guides you through all the different aspects of Physical Education teaching. It examines the nature and purpose of physical education highlighting the need for a balanced curriculum that includes gymnastics, dance, swimming, athletics and outdoor and adventurous activities. Planning, assessment and differentiation are discussed in detail alongside carefully chosen examples to demonstrate good practice. There is also a strong focus on inclusion to ensure that all your students are able to make progress and achieve. With a wealth of ready-to-use activities and techniques, this is your essential guide as you start your exciting career as an outstanding Physical Education teacher"--
The aims of physical education -- Curriculum essentials in physical education -- Planning essentials -- Assessment essentials -- Effective differentiation within PE -- Providing for the most-able within PE -- Providing for students with special education needs within PE -- Use of ICT in physical education -- Ensuring good behaviour in PE lessons -- Using action research to improve practice -- PE as a tool for improving transition/transfer -- Leadership for learning -- Improving subject knowledge -- Health and safety in PE -- From PE to community sport -- Job applications and interview advice -- Your first term in post.
Keywords: Physical education for children -- Curricula -- Great Britain; Physical education for children -- Study and teaching -- Great Britain; Physical education teachers -- Training of -- Great Britain